Experimental validation of the shakedown concept for pavement analysis and design - Juspi, Sumyaty (2007)
The shakedown concept has been widely applied in structural and mechanical engineering numerical models. The concept is related to the response of a structure to load repetitions in a resilient manner without further permanent deformation. More than 40 wheel tracking tests were conducted with various wheel load levels for each test to check the validity of the shakedown concept in the pavement foundation. Six different types of soils with different characteristics were used in the wheel tracking tests. These were a silt (from gravel pit washings), a silty-clay (Mercia Mudstone, referred to here by its earlier name of Keuper Marl), two sands (Portaway and Langford Fill), and two crushed rocks (Carboniferous Limestone and Granite). Three different sized wheel-tracking facilities were used; a small wheel tracker (SW), a larger Slab Testing Facility (STF) and the half-scale Nottingham Pavement Testing Facility (PTF). These allowed various wheel specifications and test specimen sizes to be investigated. The test programme embraced one, two and three layered systems. The permanent vertical deformation of each system was measured after a certain number of passes. The soil is said to be under shakedown if after a certain number of passes, there is no further permanent deformation. The experimental result was compared with the theoretical shakedown prediction. A series of static triaxial tests for each soil, with the test conditions close to the wheel tracking tests, was carried out to identify the shear strength to be used as input parameters for the theoretical shakedown prediction. The theoretical shakedown limits of the various soil combinations show a good agreement with the wheel tracking test results.